Pengaruh Penggunaan Cairan yang Berbeda terhadap Kualitas Organoleptik Mochi (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2025)
Mochi-based food products are increasingly popular in Indonesia due to their chewy texture and distinctive sweet taste, making them a popular snack among various groups. As consumer interest in mochi increases, innovation in the production process is crucial, particularly in the selection of liquid ingredients as one of the main components. The use of different liquids has the potential to affect the organoleptic characteristics of mochi, such as color, aroma, texture, and taste, thereby increasing the product's appeal and selling value. This study aims to analyze the effect of the type of liquid used on the organoleptic quality of mochi. The study was conducted using a quantitative approach through an experimental method using a one-factor completely randomized design (CRD) with three replications. The study sample consisted of 30 untrained panelists selected through a total sampling technique from among students of the Culinary Arts Study Program, Padang State University. The four types of liquids used for treatment were water, soy milk, coconut milk, and coconut water. Assessment was carried out using an organoleptic test with a 7-point hedonic scale, covering five aspects: color, aroma, texture, taste, and overall acceptability. Data were analyzed using a one-way ANOVA test to determine the significance of differences between treatments. The results showed that mochi with coconut water scored the highest in color (5.88), texture (6.39), flavor (6.07), and overall acceptability (5.88), while the highest aroma was obtained from mochi with soy milk (6.50). Although statistical results showed no significant difference between treatments (p > 0.05), mochi with coconut water was subjectively preferred by panelists. Therefore, coconut water is recommended as an alternative liquid ingredient that has the potential to improve mochi sensory. Therefore, coconut water is recommended as an alternative liquid ingredient that has the potential to enhance the sensory qualities of mochi.